The Possibility Of English As A Second Language In Indonesia - Adipramono, Raditya (Journal of English and Education (JEE), 2011)
It is known that there is a general concern for those who must leave their original language and original culture to adjust to the surroundings and mastering a new language. For Indonesian, English is known as first foreign language and not as second language. There are some problems as Indonesian to regard English as second language. This paper is trying to discuss the problems and also the possibility of English as second language in Indonesia.